Early parasitoid recruitment in invading cynipid galls - Schönrogge, Karsten; Moriya, Seiichi; Melika, George; Randle, Zoë; Begg, Tracey; Aebi, Alexandre; Stone, Graham N (My University, 2006)
Biological invasions are widely seen as the biggest threat to biodiversity next to the loss of habitats. One aspect of considerable interest is the recruitment of natural enemies after the establishment of the invad-ing species and how such enemies link invaders to native communities. However, not all invaders are invasive. Eight cynipid species originating in south-eastern Europe invaded Britain over the last 200 years. Presently they cause no economic concern or have any detectable detrimental effect on the native cynipid fauna. Since their invasions have been allowed to progress without intervention, they provide an excellent opportunity to study the recruitment of natural enemies and their integration into native communities. In contrast, the invasion of Japan by Dryocosmus kuriphilus from China caused great economic concern, because considerable damage to its host trees, Castanea spp. a valuable fruit tree in Japan and elsewhere in the world, is caused by high infestation rates. Here we review the early recruitment of parasitoids to the alien species in the UK and D. kuriphilus in Japan, their role in the invaders population dynamics, and how they link the invaders to native cynipid communities.
Keywords: Biological Invasions; Biological Control; Parasitoid Recruitment; Community Structures